2010
DOI: 10.1007/s00586-010-1602-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of cervical kyphosis

Abstract: Cervical kyphosis is an uncommon but potentially debilitating and challenging condition. We reviewed the etiology, presentation, clinical and radiological evaluation, and treatment of cervical kyphosis. Based on the current controversy as to the ideal mode of surgical management, we paid particular attention to the available surgical strategies. There are three approaches for cervical kyphosis: the anterior, posterior or combined procedures. The principal indication for the posterior strategy is a flexible kyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 63 publications
2
63
1
1
Order By: Relevance
“…Numerous previous reports have described osteotomy techniques for the lumbar spine that are commonly applied in an analogous fashion to the cervical spine, 15,17,36,40 and several of these would be classified within the Grade 2 osteotomy category. These include the Smith-Petersen osteotomy, 54 which involves wide resection of the posterior elements, including the lamina and bilateral facets, and, as initially described, was applied to multiple levels through previously fused facets in upper levels of the lumbar spine.…”
Section: Grade 2: Complete Facet Joint Resection/ponte Osteotomymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous reports have described osteotomy techniques for the lumbar spine that are commonly applied in an analogous fashion to the cervical spine, 15,17,36,40 and several of these would be classified within the Grade 2 osteotomy category. These include the Smith-Petersen osteotomy, 54 which involves wide resection of the posterior elements, including the lamina and bilateral facets, and, as initially described, was applied to multiple levels through previously fused facets in upper levels of the lumbar spine.…”
Section: Grade 2: Complete Facet Joint Resection/ponte Osteotomymentioning
confidence: 99%
“…Likely due to the complexity and risk of Grade 7 osteotomies, as well as the relatively limited indications, few reports of these osteotomies exist. 10,11,15,17 Nomenclature Reliability Based on the proposed nomenclature, a reliability study was performed using 25 clinical cases that were graded by 11 readers with expertise in CSD diagnosis and treatment. The readers were experienced cervical and thoracolumbar deformity surgeons and members of a large multicenter deformity study group.…”
Section: Grade 7: Complete Vertebral Column Resectionmentioning
confidence: 99%
“…Cervical kyphosis can occur as a result of iatrogenic processes or systemic arthritides such as degenerative disc disease, external trauma, neoplastic disease, infection, ankylosing spondylitis, or rheumatoid arthritis; it can also occur without underlying diseases [3]. Cervical kyphosis can cause pain in the cervical spine, neuropathic pain, and neurologic problems such as muscle weakness, sensory impairment, or gait impairment due to pressure on the spinal cord or spinal nerve roots; in severe cases, it may cause tetraplegia or respiratory difficulties [134]. Moreover, several studies have reported an association with dysphagia [23].…”
Section: Introductionmentioning
confidence: 99%
“…Stand alone posterior correction is often limited to flexible kyphotic deformities that can be reduced in a closed fashion prior to instrumented stabilization. 1 Unlike flexible deformities, fixed kyphotic deformities are treated through multistage anterior-posterior surgeries. [2][3][4] Immobile posterior facet joints prohibit sagittal correction through a single anterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…While effective, this multistage approach is labor intensive and exposes to the patient to complications arising from both anterior and posterior operations as well as prolonged anesthesia times. 1 An alternative to this three stage operation is a single stage pedicle subtraction osteotomy (PSO). A PSO releases the posterior, middle and anterior columns of the spine by resecting the facet joints, pedicles, and a portion of the vertebral body at the apex of a kyphosis through a posterior approach.…”
Section: Introductionmentioning
confidence: 99%